Contract for Public Procurement in Terms of Private Law (Law and Safety, 2021)
The authors have analyzed the way of the origin and consolidation of the public procurement procedure in the Ukrainian national law from 1993 till the present day. That allowed us to determine the main conditions of public procurement, which have not changed during the whole period of existence of the independent legal system of Ukraine, and to critically evaluate them. Namely, the basis for payment is a report on the results of public procurement during the procurement of goods, works or services, and the cost of procurement should have been equal to or have exceeded the amount of UAH 200,000.The main scientific works focused on the consideration of public procurement issues in various branches of Ukrainian law have been summarized. The concept of the contract for procurement has been generalized and its features have been listed: the contract for procurement is an agreement between the customer and the participant (most of the parties), aimed at establishing, transferring or terminating property rights and obligations, which is concluded as a result of the procurement procedure and which provides the acquisition of freehold interest in the property, provision of services or performance of works. The main conceptual contradictions between the contract for procurement, the civil contract and the commercial agreement have been established and characterized. Based on the analysis of tender, civil and commercial legislation, the authors have carried out a critical analysis of the contract for procurement in terms of understanding and essential terms of the general civil contract, namely: violation of the concept of free agreement between the parties, non-compliance with equality of the rights, unreasonable narrowing of the contract for procurement up to the provision of services, performance of works or acquisition of ownership for goods, which contradicts the draft contract included in the tender documentation, the impossibility of reducing the contract price in the direction of reduction as agreed by the parties, the lack of electronic form of the contract for procurement provided by the tender legislation.
Keywords: tender procedure; public procurement; a contract; contract for procurement; essence of contract for procurement; form of contract